Molecular heterogeneity in human papillomavirus‐dependent and ‐independent vulvar carcinogenesis. (20th July 2018) - Swarts, Dorian R. A.; Voorham, Quirinus J. M.; van Splunter, Annina P.; Wilting, Saskia M.; Sie, Daoud; Pronk, Divera; van Beurden, Marc; Heideman, Daniëlle A. M.; Snijders, Peter J. F.; Meijer, Chris J. L. M.; Steenbergen, Renske D. M.; Bleeker, Maaike C. G.
Abstract: Vulvar squamous cell carcinoma (VSCC) and precancerous vulvar intraepithelial neoplasia (VIN) can develop through human papillomavirus (HPV)‐dependent and ‐independent pathways, indicating a heterogeneous disease. Only a minority of VIN progress, but current clinicopathological classifications are insufficient to predict the cancer risk. Here we analyzed copy number alterations (CNA) to assess the molecular heterogeneity of vulvar lesions in relation to HPV and cancer risk. HPV‐status and CNA by means of whole‐genome next‐generation shallow‐sequencing were assessed in VSCC and VIN. The latter included VIN of women with associated VSCC (VIN VSCC ) and women who did not develop VSCC during follow‐up (VIN no VSCC ). HPV‐testing resulted in 41 HPV‐positive (16 VIN VSCC, 14 VIN no VSCC, and 11 VSCC) and 24 HPV‐negative (11 VIN VSCC and 13 VSCC) lesions. HPV‐positive and ‐negative VSCC showed a partially overlapping pattern of recurrent CNA, including frequent gains of 3q and 8q. In contrast, amplification of 11q13/cyclinD1 was exclusively found in HPV‐negative lesions. HPV‐negative VIN VSCC had less CNA than HPV‐negative VSCC ( P  =   .009), but shared chromosome 8 alterations. HPV‐positive VIN no VSCC had less CNA than VIN VSCC ( P  =   .022). Interestingly, 1pq gain was detected in 81% of HPV‐positive VIN VSCC and only in 21% of VIN no VSCC ( P  =   .001). In conclusion, HPV‐dependent and ‐independent vulvar carcinogenesis is characterized by distinct CNA patterns at the VIN stage, while more comparable patterns are present at the cancer stage. Cancer risk in VIN seems to be reflected by the extent of CNA, in particular chromosome 1 gain in HPV‐positive cases. Abstract : Given that vulvar (pre)cancerous lesions present as a heterogeneous disease with a minority of vulvar intraepithelial neoplasia's (VIN) progressing to cancer, there is a clinical need to identify women with VIN at risk for cancer. Using whole‐genome shallow‐sequencing on HPV‐positive and HPV‐negative VIN and vulvar squamous cell carcinoma (VSCC), we were able to identify chromosome 1 gain as a strong indicator for cancer risk in HPV‐positive VIN.